The Influence of Organizational Culture and Transformational Leadership on Employee Retention through Job Satisfaction - Radiyah Radiyah; Budi Utomo (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis Dan Studi Ekonomi Syariah, 2025)
In today’s competitive business environment, particularly in the restaurant industry, employee retention has become a significant challenge due to the high turnover rate. High employee turnover indicates low retention, which can disrupt operational stability, reduce service consistency, and negatively impact customer experience. Retention refers to an organization's ability to maintain its workforce over the long term, which is essential for sustaining business success. This study aims to examine the influence of organizational culture and transformational leadership style on employee retention, with job satisfaction as a mediating variable This research is a quantitative study using primary data collected through questionnaires. The sample consists of 60 respondents who are employees of Resto Kampoeng Banyumili. The collected data were analyzed using IBM SPSS 25. The results of the study indicate that organizational culture has a positive and significant influence on job satisfaction. Transformational leadership also has a positive and significant influence on job satisfaction. Organizational culture has a positive and significant effect on employee retention, while transformational leadership has a negative and insignificant effect on employee retention. Job satisfaction is found to have a positive and significant influence on employee retention. Path analysis results show that job satisfaction is able to mediate the relationship between organizational culture and employee retention, as well as between transformational leadership and employee retention